2019
DOI: 10.1016/j.tics.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

From Knowing to Remembering: The Semantic–Episodic Distinction

Abstract: The distinction between episodic and semantic memory was proposed in 1972 by Endel Tulving and is still of central importance in Cognitive Neuroscience today. Data obtained in the last 30 years or so, however, support the idea that the frontiers between perception and knowledge and between episodic and semantic memory are not as clear cut as previously thought, prompting a rethinking of the episodic-semantic distinction. Here, we review recent research on episodic and semantic memory, highlighting similarities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
168
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 258 publications
(200 citation statements)
references
References 181 publications
(193 reference statements)
12
168
1
Order By: Relevance
“…sensory or motor) areas to transmodal, highlevel areas 33,34 . These transmodal areas are thought to facilitate cognitive processes, such as autobiographical memory, in a content-agnostic fashion 16,32,33,[35][36][37] . Intriguingly, however, our data show that place-memory selective subregions exist within each of these default mode network hubs, broadly mirroring the category-selective subdivisions of the visual system 22,38,39 .…”
Section: Fig 1 Distinct Topology Of Place-memory and Scene-perceptimentioning
confidence: 99%
“…sensory or motor) areas to transmodal, highlevel areas 33,34 . These transmodal areas are thought to facilitate cognitive processes, such as autobiographical memory, in a content-agnostic fashion 16,32,33,[35][36][37] . Intriguingly, however, our data show that place-memory selective subregions exist within each of these default mode network hubs, broadly mirroring the category-selective subdivisions of the visual system 22,38,39 .…”
Section: Fig 1 Distinct Topology Of Place-memory and Scene-perceptimentioning
confidence: 99%
“…Semantic memory is most often defined as general, culturally shared knowledge, such as knowledge of facts, public events, concepts and people (Binder & Desai, 2011;Hart, et al, 2007;Martin, 2001;Renoult, 2016;Renoult, et al, 2019). It refers to public, accessible information with enough general awareness that it can be shared by members of a culture.…”
Section: Categories Of External Details: Separating Personal From Genmentioning
confidence: 99%
“…Given effects on inferolateral temporal lobe structures mediating semantic knowledge, we predicted that production of general semantics would be reduced in association with damage to these regions (Lambon Ralph, Jefferies, Patterson, & Rogers, 2017;Renoult, Irish, Moscovitch, & Rugg, 2019) as assessed by high resolution structural MRI. Decomposing these external details into different subcategories, Strikwerda-Brown et al (2018) reported that, in their group of dementia patients (SD and Alzheimer's), general semantic details were elevated and, in the case of SD patients, there was no difference in personal semantic details with control participants, an unexpected finding considering the prevalent impairment of semantic memory in SD (Lambon Ralph, Jefferies, Patterson, & Rogers, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A key distinction from the kind of rapid statistical learning tasks employed here is that such semantic memory-based predictions may emanate through spreading activation within neocortex, anatomically shielding them from interference by episodic encoding in the hippocampus. However, whether semantic and episodic memories can be fully dissociated remains unclear (Renoult et al, 2019), suggesting a potential interaction of prediction from semantic memory with episodic memory.…”
Section: Relation To Models Of Learning and Memorymentioning
confidence: 99%